ANALISIS KELAYAKAN USAHA BEBEK PEDAGING SISTEM SEMI KEMITRAAN - Yuhanin Zamrodah; Dena Shafia Dena Shafia; agustina widyasworo (Universitas Islam Balitar, 2024)
The development of livestock businesses in Indonesia is a part that is closely related to agricultural development which refers to economic development. The duck farming business is a good business opportunity for the Indonesian people. The semi-partnership system is a system that is almost the same as the independent system, the difference is the sales system. Production sales using a semi-partnership system are sold directly to the factory. This study is inteded to determine the feasibility analysis of a broiler duck business using a semi-partnership system through calculating the break event point (BEP) and revenue cost ratio (R/C). The research method used was observation and interviews with breeders. Observed variables include production costs, income, receipts, BEP values, and R/C values. The data obtained was then analyzed using quantitative descriptive methods. The research results show that the cost of producing broiler ducks for one year is IDR 2,071,500,000. The income received was IDR 2,409,742,000. The profit obtained was IDR 338,242,000. The resulting R/C value is 1.16, This means that the business deserves to be continued because the R/C value exceeds 1. The analysis result of the BEP unit is 82,860 kg, whereas in this study the total number of ducks harvested was 95,500 kg, this shows that the unit BEP is smaller than the production results in the research. The BEP price obtained was IDR 21,691/kg. Meanwhile, in this study the price obtained was IDR 25,000/kg, this shows the price of BEP is smaller than the price of duck in this study. From the research results can concluded that this duck farming business has made a profit judging from the BEP price analysis and R/C results so that this business is worth continuing.